Integrating technology in the classroom: how technology can enhance social studies - Perry, Lynsey Malia, author; De Miranda, Michael Anthony, author (Colorado State University. Libraries, 2006)
This poster highlights the integration of technology within the classroom, focusing on U.S. History as a content area.
Keywords: educational technology